Online Class: Its Implication Towards Academic Skills Development - T. C. Bermudez; A. M. Alcaide; A. M. Barcelona; E. Peralta; A. Malaco (Indonesian Journal of Educational Research and Technology, 2021)
We aimed to find out the students’ academic skills development through the use of descriptive research design. In the experiment, we used random sampling to determine the level of students’ online discourse skills in terms of spoken and written means as well as the level of student’s development of academic skills. This research was conducted by distributing a customized and corrected questionnaire to the validation of the online learning questionnaire with a 4-point Likert scale interpretation to determine the interpretation of the values. Findings showed that the written discourse levels are moderate with a mean of 2.972, and spoken discourse is moderate with a mean of 2.822. The four-level students’ development skills were obtained, and most of them are moderate. Academic participation was obtained with a mean of 3.118, making inferences with 3.01, text composition with a mean of 2.93, and reading with a mean of 3.00. Based on the results of multiple surveys, there is a significant relationship between the online class and the development of academic skills as implied by the Pearson correlation test result at a 5% level of significance (Sig. 0.05). It also indicates a moderate or substantial correlation or relationship with a Pearson correlation coefficient of 0.54. This study has shed light on the wariness of these educators on how this means of learning have an impact on their learning and development.